Integration, Development and Education of Artificial Intelligence in Public Safety (IDEIA-SP) - Lucena Jr., Jose Emilio de; Morandini, Marcelo; Coleti, Thiago Adriano (Companion Proceedings of the Brazilian Symposium on Information Systems (SBSI); 2025: Companion Proceedings of the 21st Brazilian Symposium on Information SystemsDO - 10.5753/sbsi_estendido.2025.246874, 2025)
This paper aims to present an integrated model for the training and implementation of Artificial Intelligence (AI) in Public Safety. The initiative, called IDEIA-SP (Integration, Development and Teaching of Artificial Intelligence in Public Safety), encompasses three pillars: integration of AI initiatives through a standardized infrastructure; development of systems, partnerships and joint scientific production; and teaching of practical knowledge about AI. IDEIA-SP expects to contribute to improving the analysis of operational and administrative data, reducing the time to resolve incidents and optimizing processes.